Implementation Of Group Investigation Learning Methods As An Effort To Improve Student Learning Outcomes In Grade III Science Learning - Linawati, Christiyana Niken (Universitas Sebelas Maret, 2022)
Through the results of observations and interviews with third-grade teachers, it was found that student learning outcomes in natural science learning about mastering the properties of objects were still under-performed. The research objective is to improve student learning outcomes in science learning for third grade students using the Investigation Group learning model. The research conducted was Classroom Action Research (PTK) in two cycles. The stages of the cycle are planning, implementation, observation and reflection. In cycle 1, only 65% of students complete. In cycle 2 students who pass experience an increase of 90%. These results indicate that the Group Investigation (GI) learning model can improve student learning outcomes, especially the Class III Science subject at SDN 2 Dagen.